Perancangan dan Pengembangan User Experience Sistem Penilaian Karyawan 360 Derajat PT. Kaltim Daya Mandiri - Humfrey Prasetyo Rapri; Retno Indah Rokhmawati; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
PT Kaltim Daya Mandiri has a total of 109 employees who are managed by the HRD department. Of course, every employee must be assessed to maintain their performance, which always increases every year. Therefore, the HRD department uses the 360 method of employee appraisal. To increase the effectiveness of employee appraisals, it is necessary to design a 360 employee appraisal website. In this project, the author's team chose to use the Design thinking method because this method focuses the user in the design process according to the needs of the customer. PT Kaltim Daya Mandiri which also focuses on its users. In the Design thinking method there are five stages, namely; Empathize (empathy), Define (determination), Ideate, Prototype, and Testing with cognitive walkthrough methods. This study resulted in a high-fidelity prototype based on an assessment using a cognitive walkthrough, on the HRD dashboard page every second the respondent takes an average completion time of 1545.3 seconds with success rate 94% and on the assessment dashboard page every second the respondent takes an average completion time of 512.5 seconds with success rate 60% from each second given task scenario.